How Far Ahead Does the Central Bank of the Republic of Turkey Look? - Umit Bulut (Journal of Central Banking Theory and Practice, 2016)
In monetary economics literature, there is an agreement that monetary policy has a lagged effect on inflation. As a result of this agreement, monetary policy reaction functions that include expected inflation, instead of current or lagged inflation, are established. On the other hand, there is uncertainty about how much time monetary policy needs to affect inflation. The purpose of this paper is to estimate empirically how far ahead the Central Bank of the Republic of Turkey looks. In other words, the paper examines whether the CBRT takes into consideration 12-month ahead inflation expectations or 24-month ahead inflation expectations while steering interest rates. According to the results of the paper, the CBRT considers 12-month ahead inflation expectations while steering interest rates.
Keywords: C22; E52; E58; 330; The Central Bank of the Republic of Turkey; lags in monetary transmission mechanism; forward-looking reaction function.